The Lower Bounds of Eight and Fourth Blocking Sets and Existence of Minimal Blocking Sets - L.Yasin Nada Yassen Kasm Yahya; Abdul Khalik (College of Education for Pure Sciences, 2007)
ABSTRACT This paper contains two main results relating to the size of eight and fourth blocking set in PG(2,16). First gives new example for (129,9)-complete arc. The second result we prove that there exists (k,13)- complete arc in PG(2,16), k≤197. We classify the minimal blocking sets of size eight in PG(2,4).We show that Rédei -type minimal blocking sets of size eight exist in PG(2, 4). Also we classify the minimal blocking sets of size ten in PG(2, 5), We obtain an example of a minimal blocking set of size ten with at most 4-secants.We show that Rédei -type minimal blocking sets of size ten exists in PG(2, 5).